The Concept of Innovation and Its Pedagogical Place - Abduvokhidova Shakhribonu Akmalovna (Genius Journals, 2022)
This article provides information about pedagogy, a brief history of the word. There is also information about innovative pedagogy, with specific facts about the importance of this concept. Adequacy of the level of knowledge about a person's mental development and upbringing is the only requirement of objectivity. It should be noted that wellknown names are also given about humanism
Keywords: Pedagogy; innovative pedagogy; traditional pedagogy; humanism